2020
DOI: 10.1080/2158379x.2020.1764805
|View full text |Cite
|
Sign up to set email alerts
|

Memory construction of former Khmer Rouge cadres: resistance to dominant discourses of genocide in Cambodia

Abstract: In the context of post-genocide Cambodia, this article explores resistance as the product of knowledge derived from the entanglement of official and personal memories of the Khmer Rouge (KR) period. By examining two public exhibitions produced by the Documentation Center of Cambodia (DC-Cam), namely, Forced Transfers: The Second Evacuation of the Khmer Rouge Regime and Life Experiences of Former Khmer Rouge Cadres, the article argues that narratives of the KR period as portrayed by the exhibits have the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As others (e.g. Hinton, 2018;Manning, 2017;Sirik, 2020) have already observed, these stories show how the narrowly prescribed ECCC narrative may fail to resonate with the experiences of many older Cambodians. The language, scope and procedures of the ECCC did not speak to these interviewees' experiences, and while the media mayat least for those with access to itcaptured an audience initially, interest has evidently faded over time.…”
Section: Initial Enthusiasmmentioning
confidence: 77%
See 1 more Smart Citation
“…As others (e.g. Hinton, 2018;Manning, 2017;Sirik, 2020) have already observed, these stories show how the narrowly prescribed ECCC narrative may fail to resonate with the experiences of many older Cambodians. The language, scope and procedures of the ECCC did not speak to these interviewees' experiences, and while the media mayat least for those with access to itcaptured an audience initially, interest has evidently faded over time.…”
Section: Initial Enthusiasmmentioning
confidence: 77%
“…Also, the binary division between victims and perpetrators that the ECCC is based upon is problematic (Ea and Sim, 2001;Sirik, 2020), and the strict time limit of the ECCC's jurisdiction (1975)(1976)(1977)(1978)(1979)) also fails to resonate with the complex personal histories of different individuals. A monk in his eighties said that during the civil war, in the lead up to the 1975 Khmer Rouge takeover, he had decided to side with the Khmer Rouge to defend his village from marauding government soldiers.…”
Section: Initial Enthusiasmmentioning
confidence: 99%
“…And there is no clearly identifiable boogeyman on which to lay the blame. As Sirik (2020: 241) has written, the position of the current governmentregarding the Khmer Rouge is ambivalent and confusing for the Khmer people. On the one hand, the Khmer Rouge were responsible for heinous crimes committed during the regime, while on the other hand, reconciliation and forgiveness are the price for peace, even if reconciliation means digging a hole in which to bury the past.…”
Section: Exposure At the Tuol Sleng Museum Of Genocidal Crimesmentioning
confidence: 99%
“…While some Cambodians from former Khmer Rouge strongholds still attempt to place blame on forces external to Cambodia, many others have begun to construct narratives of the past based on a framework of collective amnesia and shared victimhood (Path, 2015; cited by Sirik, 2020). In research conducted in 2008, Manning found that former Khmer Rouge who visited Tuol Sleng on an ECCC-organized outreach tour often blamed atrocities on the Vietnamese, or on the maneuverings of external superpowers (Manning, 2012).…”
Section: Exposure At the Tuol Sleng Museum Of Genocidal Crimesmentioning
confidence: 99%
“…85 This focus on senior leadership is also reflective of broader political strategies. 86 Since developing a "win-win" policy to encourage the deflection of KR cadres through amnesties, reconciliation, and "burying the past" in the 1990s, 87 the current government has promoted a narrative that centralizes responsibility for KR crimes on a small and specific group of perpetrators. 88 This strategy has been particularly prominent in the debates surrounding the remit and personal jurisdiction of the ECCC; the Cambodian government has consistently resisted the prosecution of any accused beyond those indicted in Case 001 (Duch) and Case 002 (Nuon Chea, Khieu Samphan, Ieng Sary and Ieng Thirith).…”
Section: Visibilitymentioning
confidence: 99%